1998
DOI: 10.1007/bf03180907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ions with different radii on the properties of lithium aluminosilicate photosensitive devitrified glasses

Abstract: The structure of strontium-and barium-containing lithium aluminosilicate photosensitive devitrified glasses andtheeffectof'Sr" andBa2+ ontheirdielectric lossisconsidered. It is established thatin order to obtaina homogeneous compact microstructure and high physicomechanical and dielectric parameters, the materials shouldhave the leastpossiblenumber of crystalline phases.All divalent oxides contammg relatively small ions (Be 2 +, Mg 2 +, Zn 2 +) and oxides containing ions with a relatively great ionic radius (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As Mg 2+ ion preferably occupy the six-coordinated oxygen sites in LAS crystalline system, their polarization does not seem to weaken the bond between the alkali metal and oxygen ions causing low dielectric loss tangent to the LAS glass. 14 At frequencies more than 400 Hz, LAS glass records high dielectric loss due to the free motion of mobile ion, causing dipolar relaxation in response to the applied electric field. 14 A peak appearing close to 700 Hz in LAS glass may be due to the said dipolar relaxation mechanism, which reduces with increasing frequency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As Mg 2+ ion preferably occupy the six-coordinated oxygen sites in LAS crystalline system, their polarization does not seem to weaken the bond between the alkali metal and oxygen ions causing low dielectric loss tangent to the LAS glass. 14 At frequencies more than 400 Hz, LAS glass records high dielectric loss due to the free motion of mobile ion, causing dipolar relaxation in response to the applied electric field. 14 A peak appearing close to 700 Hz in LAS glass may be due to the said dipolar relaxation mechanism, which reduces with increasing frequency.…”
Section: Resultsmentioning
confidence: 99%
“…14 At frequencies more than 400 Hz, LAS glass records high dielectric loss due to the free motion of mobile ion, causing dipolar relaxation in response to the applied electric field. 14 A peak appearing close to 700 Hz in LAS glass may be due to the said dipolar relaxation mechanism, which reduces with increasing frequency. In general, glasses demonstrate a high dielectric loss factor than their crystalline counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observing Figure 6b, it can be seen that the dielectric loss of the glass-ceramics treated by high-temperature crystallization is obviously lower than that of the glass sample, which may be because the crystal phase precipitated in the glass solidifies the alkali metal ions and reduces their movement under the electric field [13], thus reducing the dielectric loss.…”
Section: Xrdmentioning
confidence: 98%
“…In their study, the sample containing 3 wt% B 2 O 3 demonstrated optimal dielectric properties, with a dielectric constant of 7.2 and a dielectric loss of 1.4 × 10 −3 (test condition: 1 MHz) [12]. Krasnikov et al investigated the impact of Mg 2+ and Ba 2+ ions on the dielectric properties of lithium aluminosilicate glass-ceramics and found that the addition of Ba 2+ ions led to a lower dielectric constant [13]. Another study conducted by Hamidreza Savabieh et al focused on adjusting the crystallization process of LAS glass to obtain a hexagonal spodumene crystal phase.…”
Section: Introductionmentioning
confidence: 99%